Frameworks of Processing the Local Economic Policy by Daily Newspapers in Kingdom of Bahrain: Analytical Study - Buhammood, Amal AbdelWahab; Alrashed, Maha Sami (Journal of Humanities & Social Sciences, 2022)
This study aims at identifying the way of handling the local economic policy by the Bahraini daily newspapers, and the frameworks of processing this policy on daily newspapers as a source of information about the local economic policy.This descriptive study is based on the theoretical frameworks of mass media. The media survey methodology was used. The study used tools for collecting data content analysis.The study covered all the forms of editing in the newspapers of Akhbar Al Khaleej and Al Watan during the period from 1 April 2015 to 1 April 2018, 616 topics were analyzed.The results of the study show that:- The most important framework for the local economic policy was the decline in oil prices by (33%).- The issue of spending rationalization ranked first in the framework of solutions used by the study sample to deal with local economic policy issues at 19.5%.- The most important framework of the economic policy outcomes is the increase of the prices of goods and services by 25.1%.- The most persuasive methods used by the Bahraini newspapers are “facts and information” with a percentage of (33%).
Keywords: Daily Newspapers; Frameworks of Mass Media; Economic Policy